Bimetal organic framework capable of identifying cysteine and preparation method thereof
By synthesizing a bimetallic organic framework MOF with a periodic pore structure, ZnCoBTCHx, the problem of insufficient selectivity in amino acid discrimination in the existing technology was solved, and rapid and significant recognition of cysteine was achieved, demonstrating its application in biomedical research. application potential.
Patent Information
- Application Number
- CN202411309090.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-09-19
AI Technical Summary
The prior art is difficult to distinguish and highly selectively recognize amino acids, especially since the amino acids have the same functional groups, resulting in insufficient material selectivity for distinguishing these compounds.
Design and synthesize a three-dimensional dual-metal organic skeleton MOF, Zncobtchx, which are prepared through paradise and 1,3,5-benzony acid and metal zinc and cobalt ions to form a periodic pore structure with cyclical tubular and DNA groove channels. , Enhance the detection signal of cysteine.
ZNCOBTCHX significantly enhances the selective recognition ability of cysteine, can distinguish the-SH and -S-groups in amino acids, provides visual recognition effects, and shows major application potential in biomedical research and disease diagnosis. Essence
Smart Images

Figure CN119350638A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the fields of biomedicine and material chemistry, and in particular to a bimetallic organic framework capable of recognizing cysteine and a preparation method thereof. Background Art
[0002] Amino acids, as the basic building blocks of peptides and proteins, play a vital role in various metabolic processes and serve as biomarkers for predicting disease risk. However, since amino acids have the same functional groups (amino and carboxyl), it remains a challenge to prepare highly selective materials that distinguish these compounds. Metal-organic frameworks (MOFs) are a class of porous crystalline materials with periodic channels, usually constructed from inorganic metal ions / clusters and organic ligands. Bimetallic metal-organic frameworks generally refer to MOF structures containing two different metal ions. Since monometallic MOFs have limited and relatively single metal active sites, if a bimetallic system is introduced into MOFs, the types of metal sites can be increased and the arrangement will be more diverse. For example, the bimetallic system of Fe-ZIF and ZIF-8 is the earliest reported bimetallic MOF. The introduction of a second ion into a single Fe-ZIF has better catalytic performance after pyrolysis. This shows that bimetallic organic frameworks have certain advantages. Summary of the invention
[0003] The present invention aims to synthesize a three-dimensional bimetallic organic framework (MOF), ZnCoBTCHx, with periodic tubular and DNA-groove-like pore structures. In this framework, Co2+ and Co3+ partially replace Zn2+ on metal sites, enhancing the functionality of the active metal center. Due to the specific pore shape and size, ZnCoBTCHx exhibits rapid and significant selective recognition of cysteine (Cys), while the change is very small for methionine, which lacks a thiol group. Importantly, ZnCoBTCHx is able to distinguish between -SH and -S- groups in amino acids. This unique ability makes ZnCoBTCHx an excellent sensor for thiol enzyme activity, showing great potential for application in biomedical research and disease diagnosis.
[0004] To achieve the above-mentioned purpose, the present invention provides the following technical solutions: a bimetallic organic framework capable of recognizing cysteine, comprising the synthesis of a bimetallic MOF, ZnCoBTCHx, which is prepared by hypoxanthine, 1,3,5-benzenetricarboxylic acid, metal zinc and cobalt ions. The MOF has two unique pore geometry structures: a DNA-like groove and a tubular structure. ZnCoBTCHx significantly enhances the detection signal of cysteine, accompanied by an obvious color change in the solution, showing good selectivity. The variable valence state of cobalt in ZnCoBTCHx promotes electron transfer during the recognition process, causing the solution color to change from colorless to yellow, and the MOF to change from dark purple to light purple, thereby providing a visual recognition effect.
[0005] Preferably, the bimetallic organic framework capable of recognizing cysteine comprises the following steps:
[0006] S1. A mixture of Zn(NO3)2·6H2O (0.08 mmol), Co(NO3)2·6H2O (0.04 mmol), hypoxanthine (0.08 mmol), 1,3,5-benzenetricarboxylic acid (0.04 mmol) and DMF (5 mL) was sealed together with 1M HNO3 (1.1 mL) in a polytetrafluoroethylene autoclave and heated at 140°C for 72 hours;
[0007] S2, after cooling to room temperature at a rate of 5°C / h, dark purple crystals were obtained by filtration, with a yield of about 40% (based on hypoxanthine);
[0008] S3. Immediately install the selected suitable single crystal on a single crystal X-ray diffractometer and perform structure determination at 100K.
[0009] Preferably, the single crystal X-ray diffraction (SCXRD) analysis shows that ZnCoBTCHx crystallizes in the hexagonal space group P63 / m, and both Zn and Co ions adopt tetrahedral coordination geometry, respectively coordinating with the pyrimidine nitrogen and imidazole nitrogen in hypoxanthine, and the carboxylic acid oxygen and bridging oxygen in BTC. This coordination mode forms a three-dimensional MOF along the c-axis, showing two different channel geometries. The first type is a tubular channel with a diameter range of about to The second type has alternating large and small pores, similar to the large and small grooves of DNA, with diameters of approximately and The tubular channels have a narrow pore size distribution (ca. ), while the DNA groove-like channels showed a broader distribution (ca. ).
[0010] Preferably, through the analysis of the powder X-ray diffraction (PXRD) experimental results, it is found that the position of the diffraction peak of ZnCoBTCHx hardly changes when it is in different solvents and pH=2-13.
[0011] Preferably, the thermogravimetric analysis (TGA) shows that heating ZnCoBTCHx to above 450 degrees will cause structural decomposition.
[0012] Preferably, the full X-ray photoelectron spectroscopy (XPS) spectrum of the ZnCoBTCHx confirms the presence of Co, Zn, N, C and O in the MOF, and high-resolution XPS spectral analysis reveals that Co 2p 3 / 2 The peak is at 781.9 eV, accompanied by a satellite peak at 785.3 eV, Co2p 1 / 2 The peak is located at 797.2 eV, and the corresponding satellite peak is at 803.1 eV.
[0013] Preferably, utilizing the strong oxidizing properties of Co3+ in the ZnCoBTCHx framework, we propose that the MOF is further used to detect sulfur-containing amino acids. In a control experiment, aqueous solutions of 20 common L-amino acids were used as test samples. 5 mg of ZnCoBTCHx was soaked in 5 mL of each 1.0 mM amino acid solution and stored in the dark for 3 days. It is noteworthy that ZnCoBTCHx showed a significant color change from colorless to yellow when exposed to cysteine (Cys), while the crystal color changed from dark purple to light purple.
[0014] A method for preparing a bimetallic organic framework capable of recognizing cysteine, the preparation method comprising the following steps:
[0015] S1. A mixture of Zn(NO3)2·6H2O (0.08 mmol), Co(NO3)2·6H2O (0.04 mmol), hypoxanthine (0.08 mmol), 1,3,5-benzenetricarboxylic acid (0.04 mmol) and DMF (5 mL) was sealed together with 1M HNO3 (1.1 mL) in a polytetrafluoroethylene autoclave and heated at 140°C for 72 hours;
[0016] S2, after cooling to room temperature at a rate of 5°C / h, dark purple crystals were obtained by filtration, with a yield of about 40% (based on hypoxanthine);
[0017] S3. Immediately install the selected suitable single crystal on a single crystal X-ray diffractometer and perform structure determination at 100K.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] 1. The present invention synthesizes a three-dimensional bimetallic organic framework (MOF), ZnCoBTCHx, which has a periodic tubular and DNA-like groove channel pore structure.
[0020] 2. In this framework, Co2+ and Co3+ partially replace Zn2+ on the metal sites, enhancing the functionality of the active metal centers.
[0021] 3. Due to the specific pore shape and size, ZnCoBTCHx exhibits a rapid and significant ability to selectively recognize cysteine (Cys), while the change is very small for methionine, which lacks a thiol group.
[0022] 4. Importantly, ZnCoBTCHx can distinguish between -SH and -S- groups in amino acids. This unique ability makes ZnCoBTCHx an excellent sensor of sulfhydryl enzyme activity, showing great application potential in biomedical research and disease diagnosis. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Single crystal structure of ZnCoBTCHx (a) Asymmetric unit (b) Metal coordination mode. (c) Three-dimensional framework formed along the c-axis direction (d) Perspective view of the ZnCoBTCHx framework showing the alternating pattern of large and small pores along the a-axis;
[0024] Figure 2 (a) tubular channel and corresponding diameter distribution diagram (b) DNA groove channel and corresponding diameter distribution diagram of the present invention;
[0025] Figure 3 PXRD patterns of ZnCoBTCHx in different solvents and under different pH conditions;
[0026] Figure 4 Thermogravimetric analysis of ZnCoBTCHx;
[0027] Figure 5 XPS graph of ZnCoBTCHx (a) full spectrum (b) high-resolution spectrum of Co 2p;
[0028] Figure 6 (a) Time-dependent UV-visible absorption spectrum change after L-cysteine (0.001 mol / L) was added to ZnCoBTCHx, (b) UV spectrum of ZnCoBTCHx after being immersed in 0.001 mol / L and 0.01 mol / L L-cysteine for 2 days;
[0029] Figure 7(a) Time-dependent UV-visible absorption spectrum change after methionine (0.001 mol / L) was added to ZnCoBTCHx, (b) UV spectrum of ZnCoBTCHx after being immersed in 0.001 mol / L and 0.01 mol / L methionine for 2 days;
[0030] Figure 8 Time-dependent changes in UV-visible absorption spectrum after the addition of glutathione (0.001 mol / L) to ZnCoBTCHx. DETAILED DESCRIPTION
[0031] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] See also Figure 1-Figure 8 The present invention provides a technical solution: a bimetallic organic framework capable of recognizing cysteine, comprising the synthesis of a bimetallic MOF, ZnCoBTCHx, which is prepared by hypoxanthine, 1,3,5-benzenetricarboxylic acid, metal zinc and cobalt ions. The MOF has two unique pore geometry structures: a DNA-like groove and a tubular structure. ZnCoBTCHx significantly enhances the detection signal of cysteine, accompanied by an obvious color change in the solution, showing good selectivity. The variable valence state of cobalt in ZnCoBTCHx promotes electron transfer during the recognition process, causing the solution color to change from colorless to yellow, and the MOF to change from dark purple to light purple, thereby providing a visual recognition effect.
[0033] In this embodiment, a method for preparing a bimetallic organic framework capable of recognizing cysteine is characterized by comprising the following steps:
[0034] S1. A mixture of Zn(NO3)2·6H2O (0.08 mmol), Co(NO3)2·6H2O (0.04 mmol), hypoxanthine (0.08 mmol), 1,3,5-benzenetricarboxylic acid (0.04 mmol) and DMF (5 mL) was sealed together with 1M HNO3 (1.1 mL) in a polytetrafluoroethylene autoclave and heated at 140°C for 72 hours;
[0035] S2, after cooling to room temperature at a rate of 5°C / h, dark purple crystals were obtained by filtration, with a yield of about 40% (based on hypoxanthine);
[0036] S3. Immediately install the selected suitable single crystal on a single crystal X-ray diffractometer and perform structure determination at 100K.
[0037] In this embodiment, single crystal X-ray diffraction (SCXRD) analysis shows that ZnCoBTCHx crystallizes in the hexagonal space group P63 / m, and both Zn and Co ions adopt tetrahedral coordination geometry, coordinating with the pyrimidine nitrogen and imidazole nitrogen in hypoxanthine, and the carboxylic acid oxygen and bridging oxygen in BTC, respectively. This coordination mode forms a three-dimensional MOF along the c-axis, showing two different channel geometries (such as Figure 1 ), the first type is tubular channels with diameters ranging from approximately to The second type has alternating large and small pores, similar to the large and small grooves of DNA, with diameters of approximately and The tubular channels have a narrow pore size distribution (ca. ), while the DNA groove-like channels showed a broader distribution (ca. ),like Figure 2 shown.
[0038] In this embodiment, the results of the powder X-ray diffraction (PXRD) experiment show that the position of the diffraction peak of ZnCoBTCHx in different solvents and pH = 2-13 has almost no change, indicating that ZnCoBTCHx has high water stability and chemical stability (such as Figure 3 shown).
[0039] In this embodiment, thermogravimetric analysis (TGA) shows that heating ZnCoBTCHx to above 450 degrees will cause structural decomposition, indicating that the MOF has high thermal stability.
[0040] In this example, the full X-ray photoelectron spectroscopy (XPS) spectrum of ZnCoBTCHx confirmed the presence of Co, Zn, N, C and O in MOF (see Figure 5 a), high-resolution XPS spectra (see Figure 5 b) Analysis revealed Co 2p 3 / 2 The peak is at 781.9 eV, accompanied by a satellite peak at 785.3 eV, Co 2p 1 / 2 The peak is located at 797.2 eV, and the corresponding satellite peak is at 803.1 eV. These binding energy features indicate the oxidation states of Co(II) and Co(III), indicating that the cobalt in ZnCoBTCHx exists in a mixed valence state.
[0041] In this example, utilizing the strong oxidizing properties of Co3+ in the ZnCoBTCHx framework, we proposed that the MOF be further used to detect sulfur-containing amino acids. In a control experiment, aqueous solutions of 20 common L-amino acids were used as test samples. 5 mg of ZnCoBTCHx was soaked in 5 mL of each 1.0 mM amino acid solution and stored in the dark for 3 days. It is noteworthy that ZnCoBTCHx showed a significant color change from colorless to yellow when exposed to cysteine (Cys), while the crystal color changed from dark purple to light purple. In contrast, no significant color change was observed for other amino acids, which was clearly discernible by the naked eye. These preliminary results indicate that ZnCoBTCHx has a strong selectivity for cysteine.
[0042] Time-dependent ultraviolet-visible spectroscopy (UV-Vis) analysis showed that after the ZnCoBTCHx crystals were introduced into the 1mM cysteine (Cys) solution, the absorption peak near 200nm continued to increase and red-shifted. At the same time, a new peak appeared at 350nm, a shoulder peak was generated at 445nm and 600nm, and the color changed to yellow (such as Figure 6 ), in contrast, under the same conditions, another sulfur-containing amino acid, methionine (Met), did not show a new absorption peak, such as Figure 7 .
[0043] Figure 6 (a) Time-dependent UV-visible absorption spectrum of ZnCoBTCHx after adding L-cysteine (0.001 mol / L), measured every 2 minutes and every 1 hour after one hour. (b) UV spectrum of ZnCoBTCHx after immersion in 0.001 mol / L and 0.01 mol / L L-cysteine for 2 days.
[0044] Figure 7 (a) Time-dependent UV-visible absorption spectrum changes after methionine (0.001 mol / L) was added to ZnCoBTCHx. (b) UV spectra of ZnCoBTCHx after being immersed in 0.001 mol / L and 0.01 mol / L methionine for 2 days.
[0045] This difference prompted us to assume that it was related to the thiol group in Cys. To further verify our hypothesis, we selected a macromolecule containing thiol groups, glutathione (GSH). The results showed that ZnCoBTCHx also showed a color response to glutathione (e.g. Figure 8 ), but at a slower rate than cysteine.
[0046] Figure 8Time-dependent UV-visible absorption spectrum of ZnCoBTCHx after adding glutathione (0.001 mol / L), measured every 2 minutes and every 1 hour after one hour. (b) UV spectra of ZnCoBTCHx after immersion in 0.001 mol / L and 0.01 mol / L glutathione for 2 days.
[0047] In summary, we designed and synthesized a three-dimensional bimetallic organic framework (MOF), ZnCoBTCHx, with periodic tubular and DNA-groove-like pore structures, in which Co2+ and Co3+ partially replaced Zn2+ on metal sites, enhancing the functionality of the active metal centers. Due to the specific pore shape and size, ZnCoBTCHx exhibited rapid and significant selective recognition of cysteine (Cys), while the change was very small for methionine lacking a thiol group. Importantly, ZnCoBTCHx was able to distinguish between -SH and -S- groups in amino acids. This unique ability makes ZnCoBTCHx an excellent sensor for thiol enzyme activity, showing great potential for application in biomedical research and disease diagnosis.
[0048] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, technique, article or equipment including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, technique, article or equipment.
[0049] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A bimetallic organic framework capable of recognizing cysteine, characterized in that: It includes the synthesis of a bimetallic MOF - ZnCoBTCHx, which is prepared by hypoxanthine, 1,3,5-benzenetricarboxylic acid, and metallic zinc and cobalt ions. The MOF has two unique pore geometries: a DNA-like groove and a tubular structure. ZnCoBTCHx significantly enhances the detection signal of cysteine, accompanied by an obvious color change in the solution, showing good selectivity. The variable valence state of cobalt in ZnCoBTCHx promotes electron transfer during the recognition process, causing the solution color to change from colorless to yellow and the MOF to change from dark purple to light purple, thereby providing a visual recognition effect.
2. A method for preparing a bimetallic organic framework capable of recognizing cysteine, based on the bimetallic organic framework capable of recognizing cysteine according to claim 1, characterized in that: The following steps are involved: S1. A mixture of Zn(NO3)2·6H2O (0.08 mmol), Co(NO3)2·6H2O (0.04 mmol), hypoxanthine (0.08 mmol), 1,3,5-benzenetricarboxylic acid (0.04 mmol) and DMF (5 mL) was sealed together with 1M HNO3 (1.1 mL) in a polytetrafluoroethylene autoclave and heated at 140°C for 72 hours; S2, after cooling to room temperature at a rate of 5°C / h, dark purple crystals were obtained by filtration, with a yield of about 40% (based on hypoxanthine); S3. Immediately install the selected suitable single crystal on a single crystal X-ray diffractometer and perform structure determination at 100K.
3. A bimetallic organic framework capable of recognizing cysteine and a preparation method thereof according to claim 2, characterized in that: The single crystal X-ray diffraction (SCXRD) analysis shows that ZnCoBTCHx crystallizes in the hexagonal space group P63 / m, and both Zn and Co ions adopt tetrahedral coordination geometry, coordinating with the pyrimidine nitrogen and imidazole nitrogen in hypoxanthine, and the carboxylic acid oxygen and bridging oxygen in BTC, respectively. This coordination mode forms a three-dimensional MOF along the c-axis, showing two different channel geometries. The first type is tubular channels with diameters ranging from about to The second type has alternating large and small pores, similar to the large and small grooves of DNA, with diameters of approximately and The tubular channels have a narrow pore size distribution (ca. The DNA groove-like channels showed a broader distribution (ca.
4. A bimetallic organic framework capable of recognizing cysteine and a preparation method thereof according to claim 2, characterized in that: Through the analysis of powder X-ray diffraction (PXRD) experimental results, it was found that the position of the diffraction peak of ZnCoBTCHx hardly changed in different solvents and pH=2-13.
5. A bimetallic organic framework capable of recognizing cysteine and a preparation method thereof according to claim 2, characterized in that: The thermogravimetric analysis (TGA) showed that heating ZnCoBTCHx above 450 °C would lead to structural decomposition.
6. A bimetallic organic framework capable of recognizing cysteine and a preparation method thereof according to claim 2, characterized in that: The full X-ray photoelectron spectroscopy (XPS) spectrum of ZnCoBTCHx confirmed the presence of Co, Zn, N, C, and O in the MOF, and high-resolution XPS spectral analysis revealed that Co2p 3 / 2 The peak is at 781.9 eV, accompanied by a satellite peak at 785.3 eV, Co 2p 1 / 2 The peak is located at 797.2 eV, and the corresponding satellite peak is at 803.1 eV.
7. A bimetallic organic framework capable of recognizing cysteine and a preparation method thereof according to claim 2, characterized in that: Taking advantage of the strong oxidizing properties of Co3+ in the ZnCoBTCHx framework, we proposed that this MOF be further used to detect sulfur-containing amino acids. In a control experiment, aqueous solutions of 20 common L-amino acids were used as test samples. 5 mg of ZnCoBTCHx was soaked in 5 mL of each 1.0 mM amino acid solution and stored in the dark for 3 days. It is noteworthy that ZnCoBTCHx showed a significant color change from colorless to yellow when exposed to cysteine (Cys), while the crystal color changed from dark purple to light purple.
Citation Information
Patent Citations
Bimetal MOF (Metal Organic Framework) nano-enzyme as well as preparation method and application thereof
CN116789978A
Non-noble metal catalyst based on surface alloying and preparation method and application thereof
CN117680155A
Bimetal double-ligand metal organic light-emitting complex as well as synthesis method and application thereof
CN118290449A
Separation of hydrogen from hydrocarbons utilizing zeolitic imidazolate framework materials
SG164007A1
Open framework composites, methods for producing and using such composites
WO2015119887A1
Cited By
Dual-mode sensing material based on bimetal MOF (Metal Organic Framework) and preparation method and application of dual-mode sensing material
CN122147693A